Pengaruh Komunikasi Interpersonal Dan Motivasi Terhadap Produktivitas Kerja Pada Pegawai Dinas Pariwisata Kabupaten Kolaka - Citra Citra; Fitri Kumalasari; Suwarto Suwarto (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to determine: (1) The effect of interpersonal communication on employee work productivity at the Kolaka Regency Tourism Office, (2) The effect of motivation on employee work productivity at the Kolaka Regency Tourism Office. The sample in this study amounted to 55 respondents using a sampling technique, namely the census method. Testing research instruments using validity and reliability tests with SPSS 23.0. The research data analysis technique used the Structural Equation Modeling (SEM-PLS) method with SmartPLS 4.0. Based on the results of this study it can be seen that the interpersonal communication variable has a positive and significant effect on work productivity as indicated by a T-Statistics value of 1.694 and a P-Values ​​of 0.047 and the motivational variable has a positive and significant effect on work productivity as indicated by a T-Statistical value of 2.191 and P-Values ​​of 0.015.